Global Volunteering Exchange: Upaya Konservasi Mangrove Berbasis Masyarakat di Pantai Cemara, Desa Lembar Selatan, Lombok Barat - Diamahesa, Wastu Ayu; Dwi Hari Setyono, Bagus; Abidin, Zaenal; Idris Affandi, Rangga; Dwina Angga, Prayogi; Azhar, Fariq; Batun Citra Rahmadani, Thoy; Sumsanto, Muhammad; Diniariwisan, Damai; Hadzriil Jeeffry , Ku (Universitas Mataram, 2025)
This international mangrove conservation program implemented a Community-Based Participatory Action Research (CBPAR) approach at Cemara Beach, West Lombok, addressing 57% mangrove loss over the past decade. The collaboration between Universitas Mataram (Indonesia) and Universiti Teknologi MARA (Malaysia) engaged 35 participants (20 students, 13 lecturers, and 2 local farmers) in rehabilitating 0.5 hectares of degraded coastal area through strategic planting of 200 Rhizophora mucronata seedlings. The three-phase methodology included: (1) Pre-activity ecological surveys and stakeholder coordination, (2) Implementation combining theoretical training (mangrove ecology, planting techniques) and hands-on planting sessions with 1.5m spacing optimization, and (3) Post-activity evaluation through participant questionnaires and focus group discussions. Key innovations included experiential learning modules and the development of an Implementation Agreement for sustained institutional collaboration. Results demonstrated 82% seedling survival after 3 months, with 92% participant competency improvement in mangrove management. The program successfully integrated local knowledge (via